Periorbital Silicone Granulomatosis 30 Years after Acupuncture - Nathan Pirakitikulr; Ann Q. Tran; Armando L. Garcia; Sander R. Dubovy; Wendy W. Lee (Case Reports in Ophthalmological Medicine)
Silicone-based compounds are commonly used in many medical applications, such as coatings for needles and syringes. Foreign body granulomas are a well-recognized complication of silicone exposure; however, they may be challenging to identify without a clear history. A 61-year-old female patient without prior history of periocular injections, filler, or surgery presented to our oculoplastic clinic with multiple periocular lesions. The patient subsequently underwent excisional biopsy of two prominent lesions, which were identified as granulomas on pathology. Further questioning revealed the cause to be facial acupuncture performed decades prior, and a subsequent targeted exam identified additional lesions at other needling sites. A third lesion was subsequently excised, and there was no recurrence at the last follow-up 3 months postsurgery. Acupuncture is an increasingly common but underrecognized source of silicone exposure and can present up to several decades after exposure as a chronic granulomatous response in a characteristic multifocal pattern.